Case series of docetaxel, trastuzumab, and pertuzumab (DTP) as first line anti-HER2 therapy and ado-trastuzumab emtansine (T-DM1) as second line for recurrent or metastatic HER2-positive salivary duct carcinoma. (February 2022) - Uijen, M.J.M.; Lassche, G.; van Engen-van Grunsven, A.C.H.; Driessen, C.M.L.; van Herpen, C.M.L.
Highlights: Majority of HER2 + SDC patients responded to first-line HER2 therapy. Subsequent second-line HER2 therapy also resulted in response in majority of patients. Both treatments had an acceptable toxicity profile. Compared to DTP, less grade ≥ 3 toxicity was observed in T-DM1 treatment. Abstract: Objective: Salivary duct carcinoma (SDC) overexpresses Human Epidermal growth factor Receptor 2 (HER2) in 29–46% of cases, favoring anti-HER2 therapy. Here, we present the results of patients with recurrent or metastatic HER2-positive SDC treated with docetaxel, trastuzumab, and pertuzumab (DTP) as first line anti-HER2 therapy and subsequently ado-trastuzumab emtansine (T-DM1) in second line. Furthermore, we searched for potential biomarkers. Methods: Retrospective case series from a tertiary hospital. First line anti-HER2 treatment consisted of DTP, after progression T-DM1 was considered for patients with an adequate performance status. Objective response rate (ORR), progression-free survival (PFS) and overall survival (OS) were assessed and related to mRNA-based PI3K and MAPK signaling pathway activity scores. Results: Thirteen SDC HER2 + patients received DTP. In twelve evaluable patients, one complete response (CR) and six partial responses (PR) were observed (ORR 58%), with a median PFS of 6.9 months (95%-CI 5.3–8.5). Seven patients received subsequent T-DM1 in second line, resulting in four PR (ORR 57%), with a median PFS of 4.4 months (95%-CI 0–18.8). Median OS after start of DTP was 42.0 months (95%-CI 13.8–70.1). Grade ≥ 3 toxicity on DTP was seen in 39% of patients, and 14% on T-DM1. Highest combined PI3K and MAPK signaling was seen in the patient with CR and lowest in the patient with progressive disease on DTP. Conclusion: In R/M HER2-positive SDC patients DTP followed by T-DM1 upon progression are promising treatments, leading to responses in the majority (58%) of the patients at an acceptable toxicity profile.